An alternative computerised scoring system for amateur boxing - Mullan, A.; O'Donoghue, P. (5th World Congress of Performance Analysis of Sport, 2001)
In the current computerised scoring system for amateur boxing, 5 judges operate a peripheral scoring device pressing a red button when the red boxer is deemed to have thown a scoring punch and a blue button when the blue boxer is deemed to have thrown a scoring punch. Where 3 or more of the 5 judges press a button of a give colour within 1s, a point is scored to the boxer of that colour. The purpose of the current study is to compare an alternative system to the current system in terms of the identification of actual scoring punches made. In the alternative system, 10 judges operate the 5 peripheral devices; 5 judges operate the red buttons to score the red boxer and 5 judges operate the blue buttons to score the blue boxer. Where three or more of the 5 judges assigned to a given boxer press a button within 1s, a point is awarded to that boxer. Fifteen subjects, all of whom were official amateur boxing judges, operated the two systems for seven bouts during the Ulster Senior Boxing Championships, 2000. All seven bouts were video recorded so as a frame-by-frame analysis could determine a correct solution with which to compare the two scoring systems. A paired t-test revealed that the alternative system produced significantly more button pressing activity than the current system (t6 = 3.7, P < 0.05). However, the alternative system did not produce significantly more occasions where scores were recorded than the current system (t6 = 1.8, P > 0.05). Furthermore, the ratio of button presses to scoring button presses for the alternative system of 1 : 2.3+0.4 was significantly greater than the 1 : 2.0+0.4 for the current system (t6 = 3.0, P < 0.05). "Consistency" was defined as the number of judges (or judge pairs in the case of the alternative system) that agreed with the winner determined by the scoring system. The current system had a consistency of 4.5+0.8 which was significantly greater than the 3.0+1.2 for the alternative system (t6 = 3.2, P < 0.05). "Correctness", on the other hand, was defined as the number of judges (or judge pairs) that agreed with the winner according to the correct solution. There was no significant difference between the correctness of the current system of 3.6+1.9 and the alternative system of 3.1+1.2 (t6 = 0.9, P > 0.05). A factorial ANOVA including system and round as within-subjects effects revealed that neither system (F1,6 = 1.6, P > 0.05), round (F3,18 = 2.1, P > 0.05) nor the interaction of system and round (F3,18 = 0.7, P > 0.05) had a significant influence on the number of judges (judge pairs) agreeing with the correct solution. The results suggest that the alternative system does not record a significantly greater proportion of the actual scoring punches thrown during a bout than the current approach. The alternative system cannot, therefore, be recommended for use in the scoring of amateur boxing.